THE SOCIAL REVOLUTION OF MASSES IN UKRAINE (NATION SHALL NOT LIVE BY BREAD ALONE) - Savelyev, Yevhen (Journal of European Economy, 2017)
The author asserts that Ukraine is currently witness to a social revolution. It has started after the Orange Revolution and compensates for the incompleteness of privatization. It consists in a gradual but increasing pressure of the masses on the new owners and authorities. In opposition to «soft» methods of privatization, the economically active population has found «soft» methods of income growth by increasing demands of the employers and politicians and ignoring the uncomplying ones. The latter ones are forced to accelerate the employees’ income growth, thus bringing changes to the structure of population’s spending, expanding their participation in the recreation industry and increasing their access to benefits of civilization.